2001
DOI: 10.1046/j.1365-8711.2001.04451.x
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy-QSO correlation induced by weak gravitational lensing arising from large-scale structure

Abstract: Observational evidence shows that gravitational lensing induces an angular correlation between the distribution of galaxies and much more distant QSOs. We use weak gravitational lensing theory to calculate this angular correlation, updating previous calculations and presenting new results exploring the dependence of the correlation on the large‐scale structure. We study the dependence of the predictions on a variety of cosmological models, such as cold dark matter models, mixed dark matter models and models ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 50 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…Typical magnifications are of order 10 per cent for moderately distant sources. In addition to QSOs, certain populations of distant galaxies can also be used as sources [305,306,307,308,309,310,311,312,313].…”
Section: Cosmic Magnificationmentioning
confidence: 99%
“…Typical magnifications are of order 10 per cent for moderately distant sources. In addition to QSOs, certain populations of distant galaxies can also be used as sources [305,306,307,308,309,310,311,312,313].…”
Section: Cosmic Magnificationmentioning
confidence: 99%
“…This model is reviewed in the , and described in detail by Gaztañaga (2003, see also Myers 2003). Gaztañaga has shown that a good power‐law expression for scale‐dependent biasing of galaxies is Whilst Gaztañaga assumed that this bias corresponded to the ratio of the galaxy and matter correlation functions (see also Guimãraes et al 2001), b ( r ) =[ξ gg ( r )/ξ mm ( r )] 0.5 , we are in fact comparing the cross‐correlation of QSOs and galaxies with the galaxy autocorrelation function, and so are defining a bias function via b ( r ) =ξ gg ( r )/ξ gm ( r ). Whilst on large scales these two definitions should be equal, one expects the halo of the central galaxy to affect the shape of ξ gm ( r ) on small scales.…”
Section: Statistical Lensing Modelsmentioning
confidence: 99%
“…Improvements have recently been made on the theoretical side; i.e., Ménard et al (2003b) went beyond the linearized magnification approximation by including nonlinear corrections to the relation between the magnification and density fluctuations, and then compared their results to numerical simulations. Guimarães et al (2001) introduced a scale-dependent galaxy bias obtained from measurements of galaxy autocorrelation functions. Jain et al (2003) modeled the complex behavior of the galaxy bias using the halo-model approach, and Takada & Hamana (2003) added an estimation of the full nonlinear magnification contribution by including the magnification profile of NFW halos (Navarro, Frenk, & White 1997) in the halo-model formalism.…”
Section: Introductionmentioning
confidence: 99%